Meet your inside: endoscopic visualizations in contemporary culture - Olsén, Jan Eric (Academic Quarter | Akademisk kvarter, 2010)
Jan Eric Olsén Meet your inside – endoscopic visualizations in contemporary culture. Visualizations of the body have increasingly become the primary interface between physicians and patients. CT, MRI, PET, ultrasound, scintigraphy, laparoscopy, the list is long of the imaging technologies utilized in hospitals and clinics today. This article deals with the visualization technique described by Bordowitz, namely endoscopy. Since endoscopy is based on the visual examination of the body as such, the shift towards external mediation creates an emotional tension between our embodied sense of corporeal interiority and the live images of soft tissues projected onto TV monitors and computer screens. Drawing on the work of visual cultural scholars such as José van Dijck and Tom Gunning (van Dijck, 2005; Gunning; 2003), the article argues that the technological visualization of the inner flesh yields an estranged relation between what we see on the screen and our unseen insides. The effect of different endoscopic technologies on our perception of the inner body is illustrated with examples from clinical medicine and performance art.